2023
DOI: 10.1126/sciadv.adg6231
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive morpho-molecular imaging reveals early therapy-induced senescence in human cancer cells

Arianna Bresci,
Jeong Hee Kim,
Silvia Ghislanzoni
et al.

Abstract: Anticancer therapy screening in vitro identifies additional treatments and improves clinical outcomes. Systematically, although most tested cells respond to cues with apoptosis, an appreciable portion enters a senescent state, a critical condition potentially driving tumor resistance and relapse. Conventional screening protocols would strongly benefit from prompt identification and monitoring of therapy-induced senescent (TIS) cells in their native form. We combined complementary all-optical, label-free, and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In 2023, Bresci et al combined CARS and SRS with quantitative phase microscopy to investigate cell senescence. 162 The authors found alterations in cell volume, thickness, and dry mass in the HepG2 cells following deferoxamine or radiation treatment. Lipid droplet characteristics, such as volume and dry mass, also exhibited notable changes during treatment, indicating senescence manifestations as early as 24 h after treatment.…”
Section: ■ Imaging Drug Response Through Biochemical and Metabolic Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Bresci et al combined CARS and SRS with quantitative phase microscopy to investigate cell senescence. 162 The authors found alterations in cell volume, thickness, and dry mass in the HepG2 cells following deferoxamine or radiation treatment. Lipid droplet characteristics, such as volume and dry mass, also exhibited notable changes during treatment, indicating senescence manifestations as early as 24 h after treatment.…”
Section: ■ Imaging Drug Response Through Biochemical and Metabolic Ch...mentioning
confidence: 99%
“…Both cell lines showed a significant reduction in cytoplasmic dry mass and protein concentrations in senescence compared with proliferating interphase cells. In 2023, Bresci et al combined CARS and SRS with quantitative phase microscopy to investigate cell senescence . The authors found alterations in cell volume, thickness, and dry mass in the HepG2 cells following deferoxamine or radiation treatment.…”
Section: Imaging Drug Response Through Biochemical and Metabolic Changesmentioning
confidence: 99%
“…CARS imaging coupled with TPEF imaging also allows for simultaneous visualization of the optical redox ratio (ORR = FAD + / (NADH + FAD + )) and lipids in primary mammary epithelial cells during acini formation (Figure B). A similar approach was adopted to study mitochondrial morphology and lipid accumulation in cancer cells during therapy-induced senescence (Figure C). Moreover, a multimodal nonlinear optical system combining SRS, SHG, and TPEF was employed to simultaneously visualize protein, saturated lipid, unsaturated lipid, de novo synthesis of protein and lipid, collagen, and ORR; such multichannel imaging represents a sensitive approach with subcellular resolution to characterize cancer subtypes …”
Section: Crs Imaging Strategies For Lipidsmentioning
confidence: 99%
“…As light traverses through a sample, the various constituents scatter light differently based on their refractive index. By rotating the imaging beam around the sample in a full circle, a series of holograms are collected from multiple perspectives [28]. These collected two-dimensional (2D) holographic images, taken from different angles of illumination, are then compiled to construct a 3D RI tomogram, offering a more comprehensive view of the sample's internal structure [29].…”
Section: Introductionmentioning
confidence: 99%